Spatial Statistical Analysis for Potential Transit Oriented Development (TOD) in Jakarta Metropolitan Region - Herika Muhamad Taki; Mohamed Mahmoud H. Maatouk (UIR PRESS, 2018)
Spatial planning on Transit Oriented Development (TOD) concerns with the integration between land use and transportation aspects. However, in some places, public transport management based on transit nodes such as train services which are not well- integrated, and causing spatial chaos, especially surrounding station areas. It is essential to prepare a public transportation plan by maximizing regional potential capacity with TOD model. The purpose of this paper is to identify and prioritize potential areas for TOD using spatial statistical analysis with combined models of Geographic Information System (GIS) and Analytical Hierarchy Process (AHP) for Jakarta Metropolitan Regional (JMR), Indonesia. This paper employed two major indicators: main- and sub-indicators depending on relevant references. The weight of each indicator was determined by chosen experts. The result showed that some of the metro areas of Jakarta were highly suitable for TOD and indicated the characteristics of the development of urban areas. This paper’s outcome was useful in order to determine the potential location of TOD and was applicable to other areas within the same geographical conditions.